«RATIONALIZING» THE NOMADIC ECONOMY: THE DEVELOPMENT OF HAYMAKING IN TURGAI REGION IN THE LATE 19TH – EARLY 20TH CENTURIES (Journal of history, 2025)
This study analyzes the development of haymaking in the Turgai region during the second half of the 19th and early 20th centuries within the context of the Russian Empire's colonial policy. This research aims to examine the administrative mechanisms for introducing haymaking and its impact on the Kazakh nomadic economy. The main idea of the study is to consider haymaking as a tool for "rationalizing" the steppe economy, which led to a fundamental transformation of the economic structure and ecological balance of the region. The scientific significance is determined by a new approach to studying haymaking as an independent factor of change, rather than merely a phenomenon accompanying agriculture. The methodology is based on M. Foucault's concept of governmentality, which allows revealing the mechanisms of colonial governance through discourse about "rational" management that overcomes the "backwardness" of nomadic life. Analysis of archival materials and statistical expedition data revealed mechanisms of administrative influence (establishing mandatory hay procurement norms, distributing mowing machines, reorganizing pasture lands) and their consequences for the traditional economy, manifested in changes in herd structure favoring cattle, development of stall-feeding practices, and soil degradation in plowed territories. The value of the research lies in a comprehensive analysis of the interconnection between colonial policy, economic practices, and environmental changes.
Keywords: haymaking; pastoral animal husbandry; Turgai region; governmentality; transformation of pastoral economy